Effect of different hardness units on fatigue wear resistence of low hardenability steel. (October 2020) - Wang, Siyang; Zhou, Hong; Zhang, Peng; Chen, Huanxi; Li, Hui; Ma, Siyuan; Chang, Geng; Zhi, Benfeng; Zhao, Shizhe
Highlights: The effect of different hardness units on fatigue wear resistence was studied. Fatigue wear resistance is also related to the strengthening mode of the unit. A new fatigue wear hardening method to replace carburizing heat treatment. Abstract: Existing studies suggested that laser processing technology can enhance the hardness of units by laser melting process and solidifying process of medium and high-carbon steel, thereby significantly enhancing its wear resistance. In such a way, however, the low hardenability steel can exhibit limited fatigue wear resistance. To enhance the wear resistance, five different hardness units were fabricated in this study using laser melting, laser carburizing, and laser cladding. As the results suggested, the harder the unit is processed, the better the wear resistance will be. However, the cladding layer that contained WC particles exhibited the highest hardness, whereas in the wearing process, the particles fell off, so the wear resistance was reduced. The sample with the second hardest unit (Msic) exhibited the optimal anti-rolling fatigue wear resistance. Furthermore, this laser treatment process can to some extent substitute for the conventional carburizing heat treatment process.